2019
DOI: 10.1177/0885328219873254
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of carboxymethylcellulose hydrogel containing β-cyclodextrin–eugenol inclusion complexes for promoting diabetic wound healing

Abstract: The difficult healing of wounds caused by diabetes remains a challenging clinical problem. The activation of nuclear factor kappa-B as a key factor contributes to prolonged inflammation and inhibition of angiogenesis. As a natural antioxidant, eugenol may downregulate the lectin-like oxidized low-density lipoprotein receptor-1 and inhibit the activation of nuclear factor kappa-B in endothelial cells. However, eugenol shows poor solubility, pungent odor, and volatility, thus impeding its clinical application as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…122 EG is a yellow oily natural liquid extracted from cloves, cinnamon, and nutmeg with good antibacterial, anti-inflammatory, and antioxidation activity. 123,124 However, the applications of EG are limited because of its poor water solubility and volatility. 125,126 Li et al incorporated the inclusion complex of EG-β-CD into the CMC hydrogel to synthesize the EG-β-CD/CMC hydrogel.…”
Section: Cd-based Drug Delivery Hydrogelsmentioning
confidence: 99%
“…122 EG is a yellow oily natural liquid extracted from cloves, cinnamon, and nutmeg with good antibacterial, anti-inflammatory, and antioxidation activity. 123,124 However, the applications of EG are limited because of its poor water solubility and volatility. 125,126 Li et al incorporated the inclusion complex of EG-β-CD into the CMC hydrogel to synthesize the EG-β-CD/CMC hydrogel.…”
Section: Cd-based Drug Delivery Hydrogelsmentioning
confidence: 99%
“…In pre-clinical wound healing studies, the effect of clove oil (eugenol) has also been attributed to accelerated healing of diabetic wounds via its effects on reduced lectinlike oxidised low-density lipoprotein receptor 1/ NF-κB induced dysfunction in endothelial cells and promotion of angiogenesis 32 . Additionally, incorporation of clove oil into a wound dressing has been shown to improve wound healing via increased fibroblast migration and deposition of collagen that resulted in significantly decreased scar formation in preclinical models of wound repair in mice 14 .…”
Section: The Use Of Essential Oils In Wound Healing and Infectionmentioning
confidence: 99%
“…A recent pre-clinical in-vivo study has demonstrated that solubility and stability of eugenol (the main component of clove oil) can be significantly enhanced by the creation of a bioactive carboxy-methylcellulose (CMC) hydrogel loaded with inclusion complexes of eugenol with β-cyclodextrin (β-CD) for accelerating healing in full thickness wounds in a diabetic mouse model 32 . Encapsulating the hydrophobic eugenol with β-CD into its cavity to form inclusion complexes overcame the issues of solubility and stability, allowing slow and sustained release of eugenol (EG) from EG-β-CD/CMC hydrogel into the infected diabetic wounds 32 . Subsequently, this allowed eugenol to reduce the chronic wound inflammation and promote healing by inhibiting the secretion of inflammatory factors (TNF-α and IL-6) and promoting angiogenesis by decreasing MMP-9 and increasing VEGF respectively 32 .…”
Section: Nanomedicine Approaches For Development Of Adjunctive Therapies Containing Natural Essential and Animal Oilsmentioning
confidence: 99%
See 2 more Smart Citations